A De Novo Gain-of-Function Variant of DNM1L Causes Developmental Encephalopathy - Dong, Shangsheng; Chen, Yanjuan; Yan, Mengfang; Huang, Xiaoli; Deng, Qiannan; Liao, Jianxiang; Zhang, Ke (浪淘沙预印本平台, 2025)
Background: Variants in the dynamin 1-like (DNM1L) gene, which encodes dynamin-related protein 1 (Drp1), can cause encephalopathy due to defective mitochondrial and peroxisomal fission 1 (EMPF1) and optic atrophy 5 (OPA5), two neurodevelopmental disorders with distinct symptoms. Given the critical role of Drp1 in mitochondrial fission, it is believed that disrupted mitochondrial fission is key to EMPF1 and OPA5 pathogenesis. However, it is unclear whether other cellular defects also contribute to pathogenesis. Results: Here, we report a novel DNM1L variant (c.1994+3T>G) in an EMPF1 patient with delayed psychomotor development, microcephaly, and hypotonia but without epilepsy. This de novo, heterozygous, and intronic variant causes the retention of a DNM1L intron, leading to an aberrant Drp1 protein with a gain of toxicity. Mechanistic studies suggested that the mutant Drp1 forms aggregates and disrupts mitochondrial morphology in cultured cells. Compared to expressing the mutant protein alone, co-expressing both wild-type and mutant Drp1 causes defects at a similar level, suggesting that the mutant Drp1 can confer toxicity to wild-type proteins. Conclusions: Combined, our findings broadened the spectrum of pathogenic DNM1L variants and suggested protein aggregation as a potentially novel pathogenic contributor.